THE EFFECTIVENESS OF LAW ENFORCEMENT SANCTIONS AGAINST NARCOTICS CRIMES IN MEDAN CITY (A CASE STUDY OF DECISION NUMBER 1891/PID.SUS/2025/PN MDN) - Bobbi Hendra; Tri Reni Novita (Jurnal Ilmu Hukum dan Keadilan, 2026)
Law enforcement against narcotics crimes is an important instrument to protect society from the destructive impacts of narcotics abuse and illicit trafficking, particularly in the city of Medan, which has a high level of vulnerability. This study aims to analyze the effectiveness of the enforcement of criminal sanctions against narcotics offenders based on Decision Number 1891/Pid.Sus/2025/PN Mdn, using a normative juridical legal research method with a case study approach, supported by court decisions, interviews with judges, as well as statutory regulations and doctrines of criminal law.The results of the study indicate that the imposition of criminal sanctions has been carried out based on lawful and convincing evidence in accordance with Law Number 35 of 2009 on Narcotics, and reflects efforts to create a deterrent effect and provide protection to the public. However, the effectiveness of law enforcement is still influenced by several factors, including the quality of evidence, inter-agency coordination, limited facilities and infrastructure, low legal awareness among offenders, and high rates of recidivism. Therefore, it is necessary to strengthen sentencing consistency, rehabilitation efforts, the capacity of law enforcement officers, institutional coordination, and active community involvement in the prevention of narcotics crimes